Left atrial appendage occlusion and radiofrequency ablation in a patient with atrial fibrillation and dextrocardia: a case report - Zengfu Zhang; Xiaohong Fu; Min Guo; Jia Gao; Rui Wang (Frontiers in Cardiovascular Medicine)
BackgroundDextrocardia is a rare congenital condition, affecting approximately 1 in 10,000–12,000 individuals. When combined with atrial fibrillation (AF), it becomes even rarer. “One-stop” surgery, including combined radiofrequency ablation (RFA) and left atrial appendage occlusion (LAAO), has become a common clinical treatment for patients with AF who develop cerebral infarction despite regular oral anticoagulants. To date, no cases have been reported of patients with AF and dextrocardia undergoing the “one-stop” procedure, making this surgery particularly challenging.Case presentationAn 85-year-old dextrocardia male with total visceral inversion and persistent AF developed cerebral infarction despite regular oral anticoagulation therapy. He was referred to our hospital for RFA of AF and LAAO. The procedure was successfully performed using a three-dimensional electroanatomical mapping system (Carto3, Biosense Webster, Diamond Bar, CA, USA), intracardiac echocardiography (ICE), and x-ray, with no complications.ConclusionThis is the first reported case of a “one-stop” surgery for dextrocardia with AF. This procedure is safe and feasible with the assistance of advanced technologies such as ICE and the VIZIGO bidirectional adjustable bent sheath.